FAKTOR YANG MEMPENGARUHI EFEKTIVITAS GURU DI JENJANG SEKOLAH DASAR: TINJAUAN LITERATUR SISTEMATIS - Alza, Nadatuljannah; Kurniawati, Farida (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
Every teacher is expected to be an effective teacher because has a direct impact on students' academic performance, learning motivation, socio-emotional competence development, and self-regulated learning. However, there is currently no review that provides insights into teacher effectiveness at the primary school level. For this reason, it is crucial to produce an overview and gain insights into teacher effectiveness in primary schools. We conducted a literature review presented in the form of a systematic literature review, aimed at understanding the factors influencing teacher effectiveness at the primary level. The systematic literature review was conducted on 14 articles sourced from six databases: Scopus, Wiley, Science Direct, Emerald Insight, Taylor & Francis, and Sage Journals. From the literature analysis, we found that the factors influencing elementary school teacher effectiveness can be categorized into internal factors (teacher self-efficacy, self-esteem, teaching experience, and teacher attitude in work) and external factors (training, job relocation, peer recognition and relationships, and leadership style)